The Ancient Bridges in Scotland, and their Relation to the Roman and Mediaeval Bridges in Europe (Proceedings of the Society of Antiquaries of Scotland, 1912)
Bridge-building is a fairly modern development, for of the 1400 important road bridges in Scotland at the present time, something like 1000 have been built since 1745, while only about 200 were constructed between 1630 and 1745; and to go back to about 1630, there were then only about 220 fair-sized bridges in the whole of Scotland. Of the 220 bridges existing in Scotland in 1630, only about 67 are left in one form or another, none in their original state; all the others have been washed away or entirely rebuilt. An account of surviving Roman and mediaeval bridges in Europe is provided. There are no surviving Roman bridges in Scotland. The survey of Scottish bridges divides them into chronological periods which reflect the different manner in which money was raised to build them.